V0#025 Proposal of steel Y-column core filling with chemical around 4th storey - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the proposal of steel Y-column core filling with chemical around 4th storey of BRACU new campus building.